CONDITION OF THE DOMESTIC TOURISM SECTOR ON THE VERGE OF POLISH PRESIDENCY IN THE COUNCIL OF THE EU - Jędrzejczyk, Irena (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper concentrates on Polish presidency in the Council of the European Union as well as its priorities, important for Polish tourism sector. The major problem to be solved is such utilization of the presidency period that would cause new Polish initiatives strengthening competitiveness of the European tourism destination in the future. Polish tourism economy could be a beneficiary of such initiatives and realization of reforms and recovery plans. The paper presents results of crisis effects transmission to European tourism sector as well as evaluation of changes of the economic situation in Polish tourism market, on the verge of Polish presidency in the Council of the EU. Guidelines for the presidency were presented, included in major strategic and recovery documents, in aim to interpret them as objectives for Polish tourism sector.